Hubungan Kemandirian Belajar Siswa dan Hasil Belajar Matematika Siswa Kelas V SDN se-Kecamatan Kebumen Tahun Ajaran 2019/2020 - Kristanto, Dhimas Ilham; Ngatman, Ngatman; Suhartono, Suhartono (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The study aimed to prove positive correlation between independence in learning and mathematics learning outcomes and to determine the contribution of independence in learning to mathematics learning outcomes for fifth grade students of public elementary schools in Kebumen sub-district in academic year of2019/2020. It was a quantitative research with correlation method. The prerequisite test used linearity test and normality. Data analysis used simple correlation test and adjusted R square. It concludes that there is positive and significant relationship between independence in learning and mathematics learning outcomes with moderate correlation level which is 0.478 and independence in learning contributed 22,8% to mathematics learning outcomes.